IDENTIFICATION OF SUITABLE AREA FOR SEAWEED CULTURE IN BALI WATERS BASED ON REMOTE SENSING SATELLITE DATA - Sayidah Sulma; Anneke K.S.Manoppo; Maryani Hartuti (BRIN, 2008)
Mariculture is a part of marine and fisheries sector that has important contribution to achieve fisheries production target. Area suitability for mariculture information is necessary for coastal development management. The information can be derived using remote sensing satellite data and Geographic Information System (GIS). The aim of this research is to identify area suitability for seaweed culture in Bali waters by considering several water physical parameters. Those parameters are bathymetry, water sheltered area. Sea Surface Temperature (SST) and Total Suspended Matter (TSM). The parameters are extracted from Landsat 7-ETM and ALOS data. High temporal resolution data such as NOAA and Aqua/Terra MODIS are also used to monitor the fluctuation of SST and TSM in particular period, so the occurrence of parameter fluctuation can be anticipated. The physical parameters generated algorithms are referred to the algorithms reported in the previous research. The result shows that remote sensing data can be used to produce area suitability for seaweed culture, and Bali has 3728.87 hectare of the area.